KLEBSIELLA PNEUMONIAE NECROTIZING FASCIITIS OF THE LOWER EXTREMITY IN A 7-MONTH-OLD MALE: A CASE REPORT - Zakanito, Marelno; Saputro, Iswinarno Doso (Universitas Airlangga, 2019)
Highlights: Diagnosing necrotizing fasciitis (NF) was challenging because its symptoms may overlap with other soft tissue infections. Necrotizing Fasciitis K. Pneumoniae, a Rare Life-threatening Case. Abstract: Introduction: Klebsiella pneumoniae necrotizing fasciitis is an uncommon soft tissue infection characterized by rapidly progressing necrosis involving the skin, subcutaneous tissue, and fascia. This condition may result in gross morbidity and mortality if not treated in its early stages. In fact, the mortality rate of this condition is high, ranging from 25 to 35%. We present a case of 7-month-old male with K. pneumoniae necrotizing fasciitis of the lower extremity. Case Illustration: A 7-month-old male presented with large areas over both left and right inferior side of the lower limbs to the emergency department of Dr. Soetomo General Academic Hospital, Surabaya, Indonesia. Physical examination revealed elevated heart rate of 136 times per minute and increased body temperature of 38oC. The large areas on both lower limbs were darkened, sloughed off, and very tender to palpation. A small area over the right hand was erythematous and sloughed off. Laboratory evaluation demonstrated decreased hemoglobin of 6.2 g/dL and elevated leukocyte of 28,850 g/dL. Blood cultures demonstrated that K. pneumoniae was present. Discussion: NF is usually hard to diagnose during the initial period. The findings of NF can overlap with other soft tissue infections including cellulitis, abscess or even compartment syndrome. The clinical manifestations of NF start around a week after the initiating event, with induration and edema, followed by 24 to 48 hours later by erythema or purple discoloration and increasing local fever In the next 48 to 72 hours, the skin turns smooth, bright, and serous, or hemorrhagic blisters develop. If unproperly treated, necrosis develops, and by the fifth or sixth day, the lesion turns black with a necrotic crust. Conclusions: K. pneumoniae necrotizing fasciitis is a rare but life- threatening disease. A high index of suspicion is required for early diagnosis and treatment of this condition